Opposite response of blood vessels in the retina to 6° head-down tilt and long-duration microgravity - Giovanni Taibbi; Millennia Young; Ruchi J. Vyas; Matthew C. Murray; Shiyin Lim; Marina Predovic; Nicole M. Jacobs; Kayleigh N. Askin; Sara S. Mason; Susana B. Zanello; Gianmarco Vizzeri; Corey A. Theriot; et al. (npj Microgravity, 2021)
Abstract The Spaceflight Associated Neuro-ocular Syndrome (SANS), associated with the headward fluid shifts incurred in microgravity during long-duration missions, remains a high-priority health and performance risk for human space exploration. To help characterize the pathophysiology of SANS, NASA’s VESsel GENeration Analysis (VESGEN) software was used to map and quantify vascular adaptations in the retina before and after 70 days of bed rest at 6-degree Head-Down Tilt (HDT), a well-studied microgravity analog. Results were compared to the retinal vascular response of astronauts following 6-month missions to the International Space Station (ISS). By mixed effects modeling, the trends of vascular response were opposite. Vascular density decreased significantly in the 16 retinas of eight astronauts and in contrast, increased slightly in the ten retinas of five subjects after HDT (although with limited significance). The one astronaut retina diagnosed with SANS displayed the greatest vascular loss. Results suggest that microgravity is a major variable in the retinal mediation of fluid shifts that is not reproduced in this HDT bed rest model.